Importance of Using Feed Additives in Ruminants' Diets - Qasimi, Mohammad Ibrahim (Journal of Natural Sciences – Kabul University, 2022)
Although feed additives are not considered nutrients, the addition of these materials is important to animal diets, especially for ruminants. Currently, because the use of antibiotics as feed additives has been banned, all efforts are concentrated on finding alternatives that maintain high animal feed efficiency and improve their productive performance. Plant-origin feed additives have, to some extent, been able to fill the gaps left by the lack of antibiotic use. These additives have been able to improve digestion and metabolism in animals while minimizing the side effects for consumers of animal products. This review discusses the additives that are currently being used globally in ruminant diets.